Emotion Online - Garde-Hansen, J. author. aut Link
VII, 236 p.
Keywords: Travelling through theories of emotion and affect, this book addresses the key ways in which media studies can be brought to bear upon everyday encounters with online cultures and practices. The book takes stock of where we are emotionally with regard to the Internet in the context of other screen media.